Computational Methods for Fatigue and Fracture - Branco, Ricardo; Berto, Filippo; Wu, Shengchuan (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The development of modern numerical methods has led to significant advances in the field of fatigue and fracture, which are pivotal issues in structural integrity. Because of the permanent tendency to shorten time-to-market periods and the development cost, the use of the finite element method, extended finite element method, peridynamics, or meshless methods, among others, has represented a viable alternative to experimental methods. This Special Issue aims to focus on the new trends in computational methods to address fatigue and fracture problems. Research on innovative and successful industrial applications as well as on nonconventional numerical approaches is also addressed.